2021
DOI: 10.21203/rs.3.rs-236410/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A network pharmacology analysis on drug-like compounds from Ganoderma lucidum for alleviation of Atherosclerosis

Abstract: Background: Ganoderma lucidum (GL) is known as a potent alleviator against chronic inflammatory disease like atherosclerosis (AS), but its critical bioactive compounds and their mechanisms against AS have not been unveiled. This research aimed to identify the key compounds(s) and mechanism(s) of GL against AS through network pharmacology.Methods: The compounds from GL were identified by gas chromatography-mass spectrum (GC-MS), and SwissADME screened their physicochemical properties. Then, the gene(s) associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…OZM passes all the factors Tumorigenicity, mutagenicity, irritant, reproductive effect with green color representation 5 (Figure 1A). Overlapping Target Proteins between AID, UC, and OZM showed that 24 target proteins were overlapping between the two public databases 6 (Figure 1B). Protein-protein interaction from 24 overlapping target proteins from STRING analysis shows that 24 nodes, 123 edges, and PPI enrichment P-value was <1.0e-16.…”
Section: Drug Activity Data From Pass Online Programmentioning
confidence: 99%
“…OZM passes all the factors Tumorigenicity, mutagenicity, irritant, reproductive effect with green color representation 5 (Figure 1A). Overlapping Target Proteins between AID, UC, and OZM showed that 24 target proteins were overlapping between the two public databases 6 (Figure 1B). Protein-protein interaction from 24 overlapping target proteins from STRING analysis shows that 24 nodes, 123 edges, and PPI enrichment P-value was <1.0e-16.…”
Section: Drug Activity Data From Pass Online Programmentioning
confidence: 99%
“…Network pharmacology is a branch of system biology that explores the complex relationships among drugs, constituents, diseases and targets through pharmacology and computer analysis techniques (Oh et al, 2021; Pei et al, 2022). It is used to explore the pharmacological mechanism of drug action on various diseases (Tu et al, 2022; Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of the constituents of extracts is useful in the matching bioactive component with biomolecular targets and indirectly, the kind of diseases the extract may be potent against. In silico protein target prediction and molecular docking have been used in the selection of potential drug-like components of natural products for chemical lead discovery against many ailments and diseases (Oduselu et al, 2019;Asghar et al, 2021;Oh et al, 2021). Cola rostrata is an underutilized and uncultivated tree crop that produces crunchy tasty edible fruits; the plant belongs to the sub-family Sterculiaceae and it is one of the Cola species that are commonly called Monkey kola (Odion et al, 2013).…”
mentioning
confidence: 99%